Changes in cardiac and muscle biomarkers following an uphill-only marathon. Issue 1 (2nd January 2018) - Da Ponte, Alessandro; Giovanelli, Nicola; Antonutto, Guglielmo; Nigris, Daniele; Curcio, Francesco; Cortese, Pietro; Lazzer, Stefano
ABSTRACT: The aim of the study was to evaluate changes in cardiac troponin I levels (cTnI) and the main biomarkers of skeletal muscle damage after an uphill-only marathon, along with its relationship with athletes' physiological parameters. Twenty-two runners participated in the "Supermaratona dell'Etna" (43 km, 0–2850 m AMSL). Before and immediately after the race, body mass and hydration status were measured together with blood sampling. At the end of the race, mean cTnI increased significantly in all athletes (mean +900%), and in 52% of them the cTnI values were over the normal range. Mean creatinine and cortisol increased significantly (by 30.5% and 291.4%), while C-reactive protein levels did not change significantly. Then, an uphill-only marathon showed a significant increase in cardiac and skeletal muscle blood biomarkers of injury, and cTnI levels were not significantly correlated with age, body mass index, V̇O2 max, training status, ultra-endurance training experience, race time and blood parameters.